2018
DOI: 10.1111/1365-2656.12896
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interspecific coexistence on laying date and clutch size in two closely related species of hole‐nesting birds

Abstract: Coexistence between great tits Parus major and blue tits Cyanistes caeruleus, but also other hole-nesting taxa, constitutes a classic example of species co-occurrence resulting in potential interference and exploitation competition for food and for breeding and roosting sites. However, the spatial and temporal variations in coexistence and its consequences for competition remain poorly understood. We used an extensive database on reproduction in nest boxes by great and blue tits based on 87 study plots across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…This value is similar to changes from southern Sweden (Kallander et al 2017) and more southerly UK and Dutch populations (Visser et al 2012). This advance was also clearly independent of the number of nesting conspecifics, with the number of nestboxes provided (a strong proxy for the number of nesting attempts) and previous year's productivity (a proxy for local changes in population size), both uninformative explanatory variables, as also recently found in a broader continental study (Møller et al 2018).…”
Section: Discussionsupporting
confidence: 84%
“…This value is similar to changes from southern Sweden (Kallander et al 2017) and more southerly UK and Dutch populations (Visser et al 2012). This advance was also clearly independent of the number of nesting conspecifics, with the number of nestboxes provided (a strong proxy for the number of nesting attempts) and previous year's productivity (a proxy for local changes in population size), both uninformative explanatory variables, as also recently found in a broader continental study (Møller et al 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Great tits and blue tits (Cyanistes caeruleus) are hole-nesting bird species that compete for cavities and food. Competition intensity varies across Europe (Møller et al 2018) and between habitats (Dhondt 2011). Long-term, individualbased monitoring of these two species have been performed across Europe and two complementary approaches have been adopted to understand how they compete.…”
Section: Introductionmentioning
confidence: 99%
“…Information on latitude, longitude and altitude was provided by the authors of earlier studies or found in publications (for details see Møller et al 2014a, b2014b, 2018, Vaugoyeau et al 2016). Tree species vary significantly in timing and amount of invertebrates available for raising offspring in tits (Kennedy and Southwood 1984, Lambrechts et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…clutch size). Intra‐ and interspecific competition are known to affect laying date and clutch size in hole‐nesting birds (Dhondt 2010, 2012, Stenseth et al 2015, Møller et al 2018). However, some studies suggest that such effects of competition are significant only in specific plots or specific periods, raising questions about the generality of these phenomena, but also about their underlying causes (Alatalo and Lundberg 1984, Török and Tóth 1988, Dhondt et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation